Effect of some fungicides on Verticillium dahliae kleb. The causal agent of olive tree wilt disease.(in vitro) (Latakia University Journal -Biological Sciences Series, 2020)
This study is carried out to evaluate the efficacy of three systemic fungicides against Verticillium dahliae kleb. the causal agent of olive wilt. Colony growth rate were recorded for 27 day and inhibition percentages compared to control were calculated. Experience shows that all tested fungicides had an inhibitory effect on the mycelial growth of V.dahliae. hexaconazole caused higher inhibition of the pathogen growth 100%، 100%، 88.94% by the concentrations 1000, 100, 10 ppm respectively, followed by azoxystrobin 79.32% by the concentrations 1000 ppm, whereas fosetyl-aluminium inhibited the pathogen growth 100% ، 81.79% at the concentration 5000 , 2000 ppm. This revealed data indicate that this fungicides has potential efficacy in controlling the wilt olive by inhibiting the mycelial growth of the pathogen V. dahliae, so There is a need to confirm that efficacy in the field.